Stability Analysis of a Microgrid System With a Hybrid Offshore Wind and Ocean Energy Farm Fed to a Power Grid Through an HVDC Link - Wang, Li; Lin, Chun-Yu; Wu, Hong-Yi; Prokhorov, Anton Victorovich (IEEE transactions on industry applications, 2018)
This paper presents the stability analyzed results of a microgrid system containing an offshore wind farm (OWF), an offshore tidal farm (OTF), and a seashore wave farm (SWF) fed to an onshore power grid through a high-voltage dc (HVDC) link based on a voltage-source converter (VSC). The characteristics of the studied OWF, OTF, and SWF are simulated by an equivalent aggregated wind doubly-fed induction generator (DFIG), an equivalent aggregated tidal DFIG, and an equivalent aggregated wave permanent-magnet synchronous generator. A damping controller located at the converter station of the HVDC link is designed by using the pole-assignment approach to offer adequate damping to the studied microgrid system. A frequency-domain approach based on a linearized system model using eigenvalue analysis and a time-domain scheme based on a nonlinear system model subject to a disturbance condition are systematically achieved. It can be concluded from the simulation results that the proposed VSC-based HVDC link joined with the designed damping controller can effectively stabilize the studied microgrid system with hybrid OWF, OTF, and SWF under various disturbance conditions. The inherent fluctuations of the generated power of the microgrid system injected into the power grid can also be effectively mitigated by the proposed control scheme.